Raced and risky subjects: The interplay of racial and managerial ideologies as an expression of "colorblind" racism. - Agung‐Igusti, Rama P. (American Journal of Community Psychology, 2024)
Contemporary manifestations of race are dynamic and elusive in the forms and shapes they take. "Colourblind" racism is effective at drawing on seemingly objective and race‐neutral discourses to obfuscate racialized forms of structural exclusion. Framed by Critical Race Theory and Critical Narrative Analysis this paper presents an example from the Australian context that examines the relationships between a grassroots initiative developed by creatives from the African diaspora and two not‐for‐profit human services organizations, to illustrate how ideologies of race are enacted and obscured by managerialist ideologies and discourses of risk. Specifically, it shows how harmful dominant cultural narratives of deficit and danger transforms racialized Africans in Australia into "risky subjects." In a managerialist organization, risk must be controlled, and thus risk becomes the rationality for the control of racialized and risky subjects. Resistance to control by those subjects produces forms of organizational defensiveness that are mobilized through managerialist discourses and practices that work to structurally exclude. These findings illustrate the ways ideologies of race work alongside and through other ideological discourses and practices which render racialized dynamics of oppression race‐neutral. Highlights: Contemporary and color‐blind manifestations of racism are evasive.Ideologies of race are obscured by discourses of risk.Risk discourses contribute to racialized forms of control and structural exclusion.